Argon plasma coagulation in the treatment of post-radiotherapy rectal bleeding / Argon plasma coagulation nel trattamento della proctite emorragica causata dalla radioterapia - Tomasello, G.; Bellavia, M.; Damiamo, et al., G. (European Journal of Oncology and Environmental Health, 2012)
Introduction: Chronic radiation proctitis is often associated to radiotherapy for treatment of pelvic cancer. The most common side effect of this pathological condition is rectal bleeding but despite the great number of clinical approaches and techniques that have been employed no consensus for the management of it is available. Although prospective randomized trials about hemorrhagic radiation proctitis are still lacking, endoscopic approach delivering an Argon Plasma Coagulation (APC) seems to be a successful and available option. Patients and Methods: Sixteen patients suffering from post-radiotherapy rectal bleeding were followed. In the nine cases presenting a rectum ulcerative colitis (RUC) like endoscopic picture a 5-ASA therapeutic approach was chosen initially, followed by an APC treatment of areas of telangectasias. The other cases, presenting only areas of telangectasias, were treated only with APC. Results: 5- ASA therapy led to an improvement of inflammation state related to RUC but recurrence of rectal bleeding caused by telangectasias was observed. In these cases an additional APC treatment gave a total remission of the problem. Also in the other cases, presenting only areas of telangectasias, a remission of rectal bleeding was achieved through APC application. Conclusions: In the cases of radiation proctitis characterized by a severe compromission of rectal mucosa integrity an anti-inflammatory pharmacological therapy is necessary but not sufficient to abrogate rectal bleeding which is often caused by the presence of areas of telangectasias. In these cases a remission of the problem could be achieved through a combination of anti-inflammatory therapy (5-ASA) and APC. Argon plasma coagulation nel trattamento della proctite emorragica causata dalla radioterapia Introduzione: La proctite cronica è spesso associata a terapia radiante per il trattamento dei tumori della zona pelvica. La complicanza più comune della proctite è il sanguinamento rettale ma, nonostante le numerose tecniche utilizzate nel trattamento di tale patologia, nessuna di esse viene universalmente ritenuta la migliore. Sebbene non esistano ancora trials randomizzati sulla proctite associata a radioterapia, l’Argon Plasma Coagulation (APC) per via endoscopica sembra un’alternativa di facile realizzazione e successo. Pazienti e Metodi: Dei sedici pazienti affetti da sanguinamento rettale conseguente a radioterapia oggetto dello studio, nove manifestavano un quadro endoscopico caratteristico della rettocolite ulcerosa (RCU), sette presentavano un quadro clinico più lieve con sole aree di telangectasia. I pazienti del primo gruppo sono stati trattati inizialmente con 5-ASA e successivamente sottoposti ad APC nel tentativo di eliminare le aree di telangectasia. I pazienti del secondo gruppo sono stati sottoposti solamente ad APC. Risultati: Il trattamento con 5-ASA ha determinato un miglioramento dello stato infiammatorio correlato alla RCU ma la scomparsa del sanguinamento rettale si è osservato solo in seguito ad APC. Questa è risultata risolutiva anche nei pazienti che mostravano solamente aree di telangectasia. Conclusioni: Nei casi di proctite post-radioterapia associati ad una severa compromissione dell’integrità della mucosa rettale una terapia farmacologica antinfiammatoria è necessaria ma non sufficiente ad eliminare il sanguinamento rettale causato dalla presenza di aree di telangectasia. In questi casi la completa remissione della patologia può essere ottenuta aggiungendo alla terapia antinfiammatoria il trattamento con APC.